On the Boundedness of a Recurrence Sequence in a Banach Space
We investigate the problem of the boundedness of the following recurrence sequence in a Banach space B: \(x_n = _k = 1^∞ A_k x_n - k + y_n , n 1, x_n = α_n , n 0,\) where |y n